2012
DOI: 10.1016/j.jtcvs.2011.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of awake nonresectional versus nonawake resectional lung volume reduction surgery

Abstract: In this randomized study, awake nonresectional lung volume reduction surgery resulted in significantly shorter hospital stay than the nonawake procedure. There were no differences between study groups in physiologic improvements, freedom from contralateral treatment, and survival. We speculate that compared with the nonawake procedure, awake lung volume reduction surgery can offer similar clinical benefit but a faster postoperative recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(88 citation statements)
references
References 17 publications
(20 reference statements)
1
87
0
Order By: Relevance
“…In addition, some high-risk patients are excluded for thoracic surgery due to functional limitation, but experience has been acquired with awake non-intubated procedures in severe emphysematous patients for lungvolume reduction surgery that allows these compromised patients to be performed pulmonary resections (6,7). In a step-forward to a less invasive approach, non-intubated single-incision procedures [non-intubated single-incision video-assisted thoracic surgery (NI-SI-VATS)] are slowly expanding, mainly in Asia and Europe (8)(9)(10)(11)(12).…”
Section: Original Articlementioning
confidence: 99%
“…In addition, some high-risk patients are excluded for thoracic surgery due to functional limitation, but experience has been acquired with awake non-intubated procedures in severe emphysematous patients for lungvolume reduction surgery that allows these compromised patients to be performed pulmonary resections (6,7). In a step-forward to a less invasive approach, non-intubated single-incision procedures [non-intubated single-incision video-assisted thoracic surgery (NI-SI-VATS)] are slowly expanding, mainly in Asia and Europe (8)(9)(10)(11)(12).…”
Section: Original Articlementioning
confidence: 99%
“…The NITS technique for non-resection lung volume reduction surgery for emphysemas had also shown similar postoperative survival when compared with intubated surgery. However, NITS group had advantages with less mortality, morbidity, and shorter hospital stays (30). Similarly, awake endoscopic thymectomy via an infrasternal approach has been reported and allows the patient to eat, drink, and walk several hours postoperatively (31) without the risk associated with muscle relaxants in myasthenia gravis.…”
Section: Current Evidence Of Nits For Thoracic Proceduresmentioning
confidence: 99%
“…Moreover, Pompeo and colleagues at the Tor Vergata University also recently published a randomized control trial comparing 32 patients undergoing non-resectional lung volume reduction surgery with thoracic epidural anaesthesia against 31 patients undergoing conventional lung volume reduction surgery with general anaesthesia and found that the incidence of prolonged air leak in the former was 18.8% compared to 48.4% for the latter, while survival and improvement in post-operative pulmonary function were similar in both groups (49). The same group also compared the results of 41 patients undergoing nonresectional lung volume reduction surgery under thoracic epidural anaesthesia against 19 patients undergoing non-resectional lung volume reduction surgery under general anaesthesia, and found that the occurrence of prolonged air leak was similar between the two groups (12.1% vs 26.3%, p=0.26), which suggests that the type of lung volume reduction surgery rather than the type of anaesthesia was the main factor in determining risk of prolonged air leak(50).…”
Section: No Cut Plication (Non-resectional) Technique For Lung Volumementioning
confidence: 99%